Factors Affecting Brand Relationship Quality of Halal Food and The Mediating Role of Halal Literacy - Mussadiq Ali, Khan; Sharizal, Hashim; Muhammad Yaseen, Buttho (y Human Resource Management Academic Research Society, 2021)
Purpose: Brand relationship is an emerging phenomenon and companies are giving it a lot of importance. Islamic marketing is gaining grounds everywhere in the world and capturing a lot of attention in the countries where Muslims are in majority and even in minority. Present research aims to evaluate factors like brand experience, religiosity, price and role of halal literacy as a mediator to the brand relationship quality of halal food brands. Methodology: Survey research method has been conducted in Kuching and Kota Samarahan cities of Sarawak State, Malaysia. 270 respondents took part in this research. The partial least square method (PLS-SEM) has been used for data analysis. Findings: The findings of the research suggest that experiential value, price, and religiosity have an effect on the brand relationship quality of halal food brands. The role of halal literacy as a mediator has been found significant in respect of experiential value and religiosity, while it remained unchanged in determining the price. Research Limitation: The research has been conducted by applying cross sectional data method. The study is limited to the state of Sarawak, Malaysia and it concerns only the food products. Practical Implication: The findings of this research can be considered as a help by brand managers in formulating their marketing and business strategy. Originality/Value: This research endeavoured to explore the importance of religiosity in customer-brand relationship of halal food brands. Moreover, the concept of the mediation role of price transparency has been investigated for the first time. It indicates that this area has never been explored before in research